2019
DOI: 10.3390/app9061237
|View full text |Cite
|
Sign up to set email alerts
|

Waste Bricks Applied as Removal Agent of Basic Blue 41 from Aqueous Solutions: Base Treatment and Their Regeneration Efficiency

Abstract: Waste brick materials were applied as removal materials of basic blue 41 (BB-41) from artificially contaminated water. They were characterized by different techniques prior their use. A series of removal tests were carried out at different conditions, such as a dosage effect, pH value, initial concentrations, and chemical treatment. The removal results indicated that the two untreated waste bricks had limited removal capacities of basic blue 41, ranging from 19 to 30 mg/g. However, these values were improved u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 64 publications
(100 reference statements)
2
8
0
Order By: Relevance
“…Nevertheless, the lower removal performance at acidic values may well be related to the extra proton ions within the solution which are in concurrency with those of the basic dye cations on the removal sites of α-NiMoO 4 . Comparable outcomes were reported by Kooli et al in the examination of waste bricks utilized as favorable agents for the removal of basic blue 41 from liquid solutions [ 70 ].…”
Section: Resultsmentioning
confidence: 67%
“…Nevertheless, the lower removal performance at acidic values may well be related to the extra proton ions within the solution which are in concurrency with those of the basic dye cations on the removal sites of α-NiMoO 4 . Comparable outcomes were reported by Kooli et al in the examination of waste bricks utilized as favorable agents for the removal of basic blue 41 from liquid solutions [ 70 ].…”
Section: Resultsmentioning
confidence: 67%
“…The eosin-loaded organoclay was separated by centrifugation, washed with water and then treated into 10 mL of a cobalt nitrate solution of (10 mM) and 12 mg of oxone, for 30 min. The oxone was added into the mixture to degrade the removed eosin [33,48]. The regeneration process was repeated for seven cycles, following the same procedure.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in case of acid activation processes, two clay minerals from different origins were examined and they found to behave differently towards the acid activation process, thus leading to materials with different C 16 cation uptake properties [46,47]. The removal of a basic dye from an aqueous solution was thus also dependent on the origin of the clay used to prepare the absorbent [48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with the commercial adsorbents, the lower adsorption capacity of waste bricks inhibits their application in wastewater treatment [20]. Many physical or chemical methods could be used to improve the removal efficiency of waste bricks [21,22]. A report showed that the incorporation of TiO 2 onto waste brick could enhance the removal efficiency of Pb 2+ [22].…”
Section: Materials and Chemicalsmentioning
confidence: 99%